Geomorfologi Daerah Tapadaa dan Sekitarnya, Kabupaten Boalemo, Provinsi Gorontalo - Arifin, Yayu Indriati; Prabowo, FX Harkins Hendro; Ningrum, Sindi Wahyu Destia (-, 2025)
This study aims to describe and interpret the geomorphological characteristics of the Tapadaa region and its surroundings in Boalemo Regency, Gorontalo Province. The research focuses on identifying landforms, slope gradients, river flow patterns, and geomorphological units that develop within the study area. The methods used include analysis of the National Digital Elevation Model (DEMNAS) data, interpretation of topographic maps, and field verification. The results show that the area is divided into four main geomorphological units, namely marine plains, fluvial plains, volcanic hills, and denudational hills. The volcanic and denudational hills are characterized by steep slopes and structural control of trellis and rectangular drainage patterns, while the fluvial and marine plains are dominated by flat to gently sloping morphologies resulting from sediment deposition. Overall, the geomorphological condition of the Tapadaa region reflects a dynamic balance between endogenic and exogenic processes that shape the coastal and upland landscape of Boalemo Regency. The results of this study provide a basis for assessing geomorphological hazards such as erosion, flooding, and slope stability, and support sustainable coastal management in Boalemo Regency.